The effect of interest rates exchange rates and capital structure on share prices in tourism sub-sector companies - Sekolastika Sekolastika; Giriati Giriati; Wenny Pebrianti; Mustarudin Mustarudin; Rizani Ramadhan (Trigin Publisher, 2023)
This research aims to assess the impact of interest rates, exchange rates, and capital structure as measured by debt-equity ratio (DER) on the share prices of tourism subsector companies listed on the Indonesia Stock Exchange between 2018 and 2022. This investigation employs quantitative research methodology. This study uses secondary data from financial reports of tourism subsector companies registered on the IDX between 2008 and 2022. The sample used is nine tourism subsector companies. In this investigation, sampling was carried out using purposive sampling. Using the SPSS 26 analysis tool, the multiple linear regression statistical method was applied to the research data. It was discovered in this investigation that Interest rates have a partial positively and significant impact on stock prices. The exchange rate partially has a negative and insignificant impact on share prices, and capital structure (DER) partial positively and significant impact on share prices of tourism subsector companies partially from 2018 to 2022. In addition, it is known that variables such as interest rates, exchange rates, and capital structure (DER) simultaneously influence the share prices of tourism subsector companies from 2018 to 2022